Morocco’s agricultural system response to the dual shock of the COVID-19 crisis and drought: learnings and recommendations for the new normal - Y. Brouziyne (2024)
As the world looks forward to the new normal after the COVID-19 pandemic, reshaping the agricultural sector and food system is a high priority of most governments. This task is strategic for Morocco due to the vital socioeconomic role of this sector in the kingdom and because of the dual shocks that hit the sector during the 2019/2020 season. This paper aimed to uncover some of the responses of Morocco’s agricultural sector to the pandemic and the low rainfall, with a focus on potential opportunities for improvement. Under the increasing recurrence of crises and shocks, systems and organisations are becoming obligated to develop resilience. The Moroccan agricultural system is expected to become more resilient to climate change-induced extremes and the volatility of global food product markets while decreasing its dependence on the international agro-inputs supply chain. Moreover, Morocco’s agricultural system should learn to evolve under uncertainty. To succeed in this task, a high level of agility is required across all components of its value chain. Specific leadership and mechanisms should be set up to increase the system's agility in responding to the unpredictable climate and consumer habits; research and development can play an important role in this. Digitalisation can also be a driver of both resilience and agility if adopted across the whole value chain.